Control of Rapid Acceleration in a Planar Legged Robot - Mailer, Christopher (Department of Electrical Engineering, 2024)
This thesis details the hardware and control design of Kemba: a planar legged robot intended for investigating bounding and explosive, agile manoeuvres. The robot incorporates both pneumatically actuated knees for powerful, compliant, and impact resistant actuation, and proprioceptive electric actuators at the shoulder and hip for high bandwidth torque control and foot placement. Kemba is capable of bounding at up to 1.7m/s with a full flight phase, jumping just under 1mhigh (2.2 times it's nominal leg length), and accelerating from rest into a top speed bound in only 2 strides and under half a second, demonstrating its agility. Stable bounding and acceleration is achieved using a discrete body oscillation stabiliser, and the more dynamic jumping and somersault motions are generated using offline nonlinear trajectory optimisation. The optimal jumping motion was executed on the physical robot while the somersault is currently still limited to simulation. Due to the unique design and actuator combination, contact implicit trajectory optimisation served as a vital tool for motion identification and controller design. In addition to the robot dynamics and unilateral contact constraints, a more tractable pneumatic actuator model was developed which enabled the numerically stiff, discontinuous air dynamics and discrete valve switching to also be incorporated into the trajectory optimisation formulation. Trajectories resulting from optimisation were accurate enough to be implemented directly on the hardware in the case of the jump motion, and also crucially inform the design of the accelerate from rest controller. The results presented in this work indicate that Kemba is a robust and agile platform, well suited for future work in understanding dynamic manoeuvres and optimal control